Maternal Life Satisfaction and Child Outcomes: Are They Related? - Eva M. Berger; C. Katharina Spieß (Deutsches Institut für Wirtschaftsforschung (DIW), 2009)
This paper investigates the association between maternal life satisfaction and the developmental functioning of two- to three-year-old children as well as the socio-emotional behaviorof five- to six-year-old children. We use data from the German Socio-Economic Panel Study (SOEP), which allows us to control for a rich set of child and parental characteristics and to use the mother's life satisfaction before the birth of her child as an instrument to eliminate potential reverse causality. The results indicate that the more satisfied the mother, the better her child's verbal skills and the lower his or her socio-emotional problems. The relation is more pronounced for boys than for girls. The results are robust even when mothers' personality or mothers' cognitive skills are controlled for.
Keywords: J13; I22; 330; Life satisfaction; subjective well-being; mothers; children; child development; skill formation; instrumental variable